THE EFFECT OF WORKLOAD ON STRESS LEVELS EMPLOYEES AT THE NIAS HERITAGE MUSEUM - Ifoni Eksaudia Telaumbanua; Fatolosa Hulu; Syah Abadi Mendrofa; Meiman Hidayat Waruwu (LPPM YPITI, 2026)
This study was conducted to determine the effect of workload on employee stress levels at the Nias Heritage Museum. The background of this study began with the phenomenon of increasing employee complaints related to work pressure, physical fatigue, health problems, and symptoms of psychological stress that arise due to high and unbalanced workloads. Excessive workloads, whether physical, mental, or emotional, are suspected to be the main factor causing work stress. This study used a quantitative method with a descriptive approach. The population in this study were all 40 employees of the Nias Heritage Museum. Data collection was carried out through distributing questionnaires using a Likert scale, and analyzed by simple linear regression using SPSS version 26. The test results showed that workload had a positive and significant effect on stress levels. The significance value of the t test was 0.000 (<0.05) and the calculated t value was 15.890 > t table 0.304 indicating that the higher the workload received, the higher the employee stress level. The calculation result of the coefficient of determination (Adjusted R²) of 86.5% indicates that workload contributes 86.5% to job stress, while the remaining 13.5% is influenced by other factors outside this study. This study recommends that the management of the Nias Heritage Museum evaluate the distribution of tasks and create a more balanced and supportive work environment to reduce employee stress levels.